Things have gotten worse since we last spoke, and other misfortunes - LaRocca, Eric (Titan Books, 2022)
Three dark and disturbing horror stories from an astonishing new voice, including the viral-sensation tale of obsession, Things Have Gotten Worse Since We Last Spoke. For fans of Kathe Koja, Clive Barker and Stephen Graham Jones. Winner of the Splatterpunk Award for Best Novella. A whirlpool of darkness churns at the heart of a macabre ballet between two lonely young women in an internet chat room in the early 2000s--a darkness that threatens to forever transform them once they finally succumb to their most horrific desires. A couple isolate themselves on a remote island in an attempt to recover from their teenage son's death, when a mysterious young man knocks on their door during a storm... And a man confronts his neighbour when he discovers a strange object in his back yard, only to be drawn into an ever-more dangerous game. Three devastating, beautifully written horror stories from one of the genre's most cutting-edge voices. What have you done today to deserve your eyes?